THE MINIMUM SERVICE STANDARDS AND SOCIAL SERVICE CHALLENGES: A CASE STUDY IN GORONTALO PROVINCE - Erfirmansyah Soedjono Adam; Arifin Tahir, Zuchri Abdussamad, Udin Hamim, Yanti Aneta (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the implementation of the Minimum Service Standards (SPM) policy in the social sector in Gorontalo Province, highlighting the main challenges, strategies implemented, and achievements that have been achieved. Limited budget, human resources, and infrastructure are the main obstacles in the implementation of optimal basic social services. To overcome these obstacles, the local government adopted a collaborative strategy through cooperation with social institutions, such as Baznas, to cover the funding gap that was not accommodated in the Regional Revenue and Expenditure Budget.. Policy implementation is carried out in accordance with the stages determined by national regulations, starting from collecting data on needs to monitoring and evaluation. The monitoring approach uses direct coordination meetings and the use of application-based technology, which facilitates reporting and supervision. The results of the study show an increase in policy implementation, although there are still gaps that require improvement, especially in terms of funding, increasing human resource capacity, and cross-sector coordination. Therefore, it is necessary to strengthen the implementation strategy and commitment from various parties to ensure quality, equitable, and sustainable social services.